Implementation Of Triplex Raw Material Inventory Control In The Fine Arts Gallery - Oktaviyah, Nurafni; Ryketeng, Masdar (Universitas Negeri Makassar, 2023)
ABSTRACT Abstract. Fine Arts Gallery has planned the supply of raw materials using only estimates, without proper planning, so the problem that the company always faces is that the costs incurred both for buying raw materials and storage costs are still very high. The type of data in this study uses qualitative data, namely data that is not in the form of numbers, such as information about the history of the company's establishment and quantitative data, namely data in the form of numbers, including data on the amount of raw material requirements in 2020, and data on ordering costs in 2020 Based on research conducted at the Fine Arts Gallery using the EOQ method, the most economical number of raw material purchases is 21 units with an order frequency of 24 times in one year with a total order cost in a year of IDR 3,552,000, the optimal total inventory cost is amounting to Rp 3,727,500, and a year's total inventory cost of Rp 7,279,500. Keywords: economic quantities, raw materials, supplies Abstrak. Fine Arts Gallery melakukan perencanan persediaan bahan baku hanya menggunakan perkiraan, tanpa adanya perencanaan yang tepat, sehingga masalah yang selalu dihadapi oleh perusahaan tersebut adalah biaya yang dikeluarkan baik untuk membeli bahan baku maupun biaya penyimpanan masih sangat tinggi. Jenis data dalam penelitian ini menggunakan data kualitatif yaitu data yang tidak berupa angka, seperti informasi tentang sejarah berdirinya perusahaan dan data kuantitatif yaitu data yang berupa angka-angka, meliputi seperti data jumlah kebutuhan bahan baku pada tahun 2020 dan data biaya pemesanan pada tahun 2020. Berdasarkan penelitian yang dilakukan pada Fine Arts Gallery dengan menggunakan metode EOQ jumlah pembelian bahan baku yang paling ekonomis adalah 21 unit dengan frekuensi pemesanan sebanyak 24 kali pemesanan dalam satu tahun dengan total biaya pesanan dalam setahun Rp 3.552.000, Total biaya persediaan yang optimal adalah sebesar Rp 3.727.500, dan total biaya persediaan setahun sebesar Rp 7.279.500. Kata kunci: Bahan baku, persediaan, kuantitas ekonomi